Identification of two novel HLA‐DQB1*03:01:01 intronic variants: HLA‐DQB1*03:01:01:47 and ‐DQB1*03:01:01:48. (27th December 2022) - Gil Etayo, Francisco Javier; Niño Ramírez, Jairo Eduardo; Vicente Parra, Ariadna; García Sanz, Ramón; Tejeda Velarde, Amalia
Abstract : Two different single nucleotide substitutions in intron 1 give rise to the alleles HLA‐ DQB1*03:01:01:47 and DQB1*03:01:01:48 .